Evaluation of Mean Thrombocyte Volumes in Asthma Patients During Acute Exacerbations and Stable Periods - Dolap, Uysal; Tug, Tuncer; Konuk, Suat (Archives of Clinical and Biomedical Research, 2018)
Objective: Asthma is a heterogeneous disease characterized by chronic airway inflammation. Mean Platelet Volume (MPV) is one of the markers of platelet activation. The disease activity has been shown to have an important role as a marker for the efficacy of anti-inflammatory therapy and inflammation. The aim of this study was to investigate the relationship between disease activity and mean platelet volume and to determine the mean platelet volume (MPV) and CRP values during asthma exacerbations and stable periods. Methods: In this study, data from 50 patients with asthma exacerbations, 50 stable asthmatic patients and 40 healthy subjects were evaluated retrospectively. Results: Even though the MPV values of patients with an asthma exacerbation was lower (9.2 ± 0.9 fL) than those of stable asthmatic patients (9.6 ± 1.3 fL), we did not find statistical differences between the groups in terms of MPV results (P = 0.374). Leukocyte, neutrophil counts and percentages and CRP levels were significantly higher in patients with an exacerbation than in stable asthmatic and control groups (p = 0.000). There was no difference in , neutrophil counts and percentages and CRP levels between stable asthmatic patients and healthy controls (p> 0.05). Conclusion: In conclusion, there was no statistically significant relationship between the MPV values and disease activity in asthmatic patients. We believe that prospective studies involving a larger number of patients are needed to determine the place of MPV in asthmatic patients, since the number of patients and controls in our study was low.